Evaluasi Penerapan Lean Six Sigma Terhadap Ruang Operasi Di Rumah Sakit : Literature Review - Tania Rahmayanti; Muhammad Fawwaz; Anisya Febriyanti; Acim Heri Iswanto (STIKes Ibnu Sina Ajibarang, 2023)
The operating room in a hospital is the most complicated in terms of management and has the biggest cost in terms of health facilities. Lean six sigma as an approach to the management to improve service and speed up service. This study aims to determine the application of lean six sigma in the operating room at the hospital. The research design used in this study was a literature review using Google Scholar to search for previous related articles. The criteria for related articles used are those published from 2019-2023 from a total of 6 journals have collected. Based on these journals, the application of lean six sigma in the operating room has a positive impact on performance efficiency that can benefit the hospital.